Integrative Analysis of m6A Regulator-Mediated RNA Methylation Modification Patterns and Immune Characteristics in Lupus Nephritis - Zhao, Huanhuan; Pan, Shaokang; Duan, Jiayu; Liu, Fengxun; Li, Guangpu; Liu, Dongwei; Liu, Zhangsuo (Frontiers in Cell and Developmental Biology, 2021)
Background: There is growing evidence to demonstrate that the epigenetic regulation of immune characteristics, especially for N6-methyladenosine (m6A) RNA methylation. However, how m6A methylation is involved in lupus nephritis (LN) is still unclear. This study aimed to determine the role of m6A RNA methylation and their association with the immune microenvironment in LN. Methods: In total, 87 glomeruli (73 LN, 14 living healthy donors), 110 tubulointerstitium (95 LN, 15 living healthy donors), and 21 kidney whole tissue samples (14 LN, 7 controls) were included in our research to evaluate the expression levels of m6A regulators. CIBERSORT was used to assess the abundance of infiltrating immunocytes. The m6A regulator gene signature for LN was identified using LASSO-logistic regression and verified with external data. Consensus clustering algorithms were used for the unsupervised cluster analysis of m6A modification patterns in LN. Single-sample gene-set enrichment analysis and gene set variation analysis algorithms were employed to assess the activity of immune responses and other functional pathways. Weighted gene co-expression network analysis and protein-protein interaction networks were used to identify m6A methylation markers. Lastly, the Nephroseq V5 tool was used to analyze the correlation between m6A markers and renal function. Results: We found that the expression of m6A regulators was more significantly different in the glomeruli in LN compared with tubulointerstitium and whole kidney tissue. We established an m6A regulator signature, comprised of METTL3, WTAP, YTHDC2, YTHDF1, FMR1, and FTO, that can easily distinguish LN and healthy individuals. Two distinct m6A modification patterns based on 18 m6A regulators were determined, with significant differences in m6A regulator expression, immune microenvironment, biological functional pathways, and clinical characteristics. Activated NK cells, most immune responses, and HLA genes had strong correlations with m6A regulators. Seven m6A markers were identified and demonstrated a meaningful correlation with GFR, indicating that they are potential prognostic biomarkers. Conclusions: This study emphasized that m6A RNA methylation and the immune microenvironment are closely linked in LN. A better understanding of m6A modification patterns provide a basis for the development of novel therapeutic options for LN.